Compassion and patient-centered medicine: convergences between the Dalai Lama Tenzin Gyatso and Ian McWhinney - Wenceslau, Leandro David (2016)
The patient-centered clinical method (PCCM) is a proposal of reorienting contemporary medical practice that identifies a distance from the patients’ subjective and qualitative experiences. To overcome this gap, the PCCM uses theories and techniques from several schools of modern Western psychology. In this paper, we analyze possible contributions to the PCCM from an Eastern school of thought - Tibetan Buddhism - using the perspective of its current spiritual leader, Tenzin Gyatso, the fourteenth Dalai Lama. Additionally, elements of Ian McWhinney’s work mediate and enrich this reflection. The development of compassion is the fundamental quality to manage the psychosocial dimension of human suffering. The PCCM and the Buddhist ethical approach, delineated by the Dalai Lama, share a common goal: understanding and non-reductionist management of human suffering. In both cases, we identify recognition and valuing the mental and emotional aspects of human relations as a strategy to achieve this comprehensive approach.